L’apport du jardinage urbain de Russie à la théorisation de l’agriculture urbaine - Louiza Boukharaeva; Marcel Marloie (VertigO)
The main object of this article is the collective urban gardening of Russia, with references to the other types of gardening made by the inhabitants of cities on urban, outer-urban, agricultural, building or not building grounds. The urban gardening of Russia brings essential references for the theorization of the urban agriculture). It is a family urban agriculture (FUA) in the sense of extra-professional activity practised by urban and not by farmers. It is a not trade activity established by the State, the companies and the population. It serves as regulating plug of the crises, by combining the functions relative to the food production, health, rest, leisure activities, education of the children, artistic creation. The conquest of the right to build a house on the plots of land of the collective gardens was a shape of democratization of the access of the urban to the ground and to the nature. It is a treatment of poverty by the generalization of an element of the lifestyle of the middle class.